2018
DOI: 10.22631/ijbmph.2018.56100
|View full text |Cite
|
Sign up to set email alerts
|

Self-care behaviors and related factors in chronic heart failure patients

Abstract: Introduction: Heart failure is a chronic disease that requires special lifelong self-care behaviors. These patients require to have self-care behaviors to confront their disease problems. Therefore, this study was designed and conducted to determine the status of self-care behaviors and its related factors. Methods: This cross-sectional study was conducted on 150 patients with chronic heart failure who were chosen purposively and were hospitalized in the cardiac wards of Tohid hospital in Sanandaj. Data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
(17 reference statements)
2
6
0
2
Order By: Relevance
“…Yapılmış bir çalışmada yaş, cinsiyet, meslek, medeni durum, sigara, ilaç ve alkol kullanımı ile öz bakım davranışları arasında ilişki bulunmazken, eğitim düzeyi, ikamet yeri ve hastalık hakkında eğitim alma durumu gibi faktörlerle ilişki olduğu belirtilmektedir. [22] Ayrıca, öz bakım gücü toplam puanı ile tedavi şekli, NYHA sınıflaması, sol ve sağ ventrikül ejeksiyon fraksiyonu arasında ilişki bulunmaktadır. Literatürde NYHA sınıf III-IV kalp yetersizliği olan hastaların kronik yorgunluktan şikayetçi olduğu belirtilmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Yapılmış bir çalışmada yaş, cinsiyet, meslek, medeni durum, sigara, ilaç ve alkol kullanımı ile öz bakım davranışları arasında ilişki bulunmazken, eğitim düzeyi, ikamet yeri ve hastalık hakkında eğitim alma durumu gibi faktörlerle ilişki olduğu belirtilmektedir. [22] Ayrıca, öz bakım gücü toplam puanı ile tedavi şekli, NYHA sınıflaması, sol ve sağ ventrikül ejeksiyon fraksiyonu arasında ilişki bulunmaktadır. Literatürde NYHA sınıf III-IV kalp yetersizliği olan hastaların kronik yorgunluktan şikayetçi olduğu belirtilmektedir.…”
Section: Discussionunclassified
“…[24] Bu çalışmalardan farklı olarak ise, Bagheri-Saweh ve arkadaşlarının (2018) çalışmasında hastalık sınıfı ve öz bakım davranışları arasında fark bulunmamaktadır. [22] Çalışmamızda hastaların yaklaşık yarısının (%47.7) hafif kısıtlı NYHA sınıfında (sınıf II) yer almasının ve yaş ortalamasının yüksek olmamasının öz bakım gücünün iyi olmasında etkili olabileceği düşünülmektedir.…”
Section: Discussionunclassified
“…The study of Bagheri Saveh et al showed that the level of self-care behaviours by patients was mostly moderate and the level of education and living and education about the disease had a signi cant relationship. As a result, the level of self-care behaviours in patients with heart failure was not satisfactory, so training and strengthening self-care behaviours in these patients is necessary [29]. In Zeighami Mohammadi et al…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Several factors that contribute to self-care behavior include patients' sociodemographic factors, knowledge of HF, and physical activity levels. [8][9][10] A previous study suggested that depression, cognitive function, and patients' cognitive function are the predictors of self-care behavior. 11 The identification of these predictors is essential to support the formulation of effective educational strategies to meet individuals' needs.…”
Section: Introductionmentioning
confidence: 99%